PERBANDINGAN TATA NEGARA INDONESIA DENGAN BRUNEI DARUSSALAM: ANALISIS SISTEM PEMERINTAHAN DAN PEMBAGIAN KEKUASAAN - Mutia Salsabila; Rika Jamin Marbun; Cynthia Aulia Dzaki; Kayla Putri Adnin (Journal of Innovation Research and Knowledge, 2025)
Each country forms its own state system. So each country has varying characteristics, this is in accordance with the conditions that affect the country itself. From a historical, cultural, social, and political perspective. Understanding the state system of another nation requires comparison. This study will compare the government systems of Indonesia and Brunei Darussalam and the principles of their distribution of power. This study uses normative juridical research techniques to disseminate relevant rules or laws and literature such as mass media, bold journals, expert opinions, and books. Although located in Southeast Asia, Indonesia and Brunei Darussalam have separate governments. According to the 1945 Constitution Article 4 paragraph (1), the president is the head of state and head of government in Indonesia, and the king or sultan holds absolute power in Brunei Darussalam. Indonesia follows the trias politica Division of power and checks and balances with equal power for the legislative, executive, and judicial institutions to supervise and unify each other. Brunei Darussalam also has executive, legislative, and judicial institutions, but all obedience is due to the Sultan, particularly the executive and legislative branches, in which the Sultan participates in these authorities. The system of government and the division of power serve to maintain the relationship between citizens and the state. This is crucial for making governance more efficient and effective. In the context of a constantly evolving world, these two countries must continually adapt to current developments and improve the quality of governance to achieve the well-being of their citizens.